Impact of marketing mix elements on consumer buying behavior toward sport products / Mohamad Hafizuddin Mat Hussin - Mat Hussin, Mohamad Hafizuddin (2018)
The purpose of this research is to examine the impact of marketing mix elements influencing consumer buying behavior towards sport products. The quantitative research method will be applied in this study. The sample of this study was community in Seremban. The total respondents will comprise of 429 and pilot study will be distributed to 43 students Faculty Sport Science and Recreation at UiTM Seremban 3. To analyze the data analysis will be used are descriptive analysis will be used to detennine factor, Independent t-Test to detennine differentiate between variables and Linear Regression to detem1ine the relationship between variables. For the purpose of the study, the questionnaire was adopted and adapt from Andreati. Zhafira, Akmal & Kumar. (2013). The result showed the highest mean of marketing mix elements is “promotion” (M = 4.07. SD =.60). The differences of marketing mix elements on consumer buying behaviour toward sport products based on gender showed there is a significant difference based on gender in the four elements of marketing mix elements. Therefore “product” has a significant in impact of marketing mix elements on consumer buying behaviour toward sport products were p value p<0.05. Overall, study in impact of marketing mix elements on consumer buying behaviour toward sport products helping the organization to manage their marketing plan.